(untitled) (Research, Society and Development, 2022)
Objective: The aim of this study was to investigate cases of Urinary tract infection (UTI) and Asymptomatic bacteriuria (ASB) in pregnant women in a Brazilian city, as well as identify the pathogens causing these diseases and its antimicrobial susceptibility profile. Also, we investigated the antibiotic therapy used in pregnant women to treat UTI and ASB, and the comorbidities which can be related to increased risk of these type of infection. Methods: This study was prospective research, descriptive and exploratory, with a qualitative approach, conducted among 35 pregnant women from October 2019 at Basic Health Unit (BHU) in Diadema, São Paulo, Brazil. Patient’s data were obtained using specific terms in the search filters from data base of BHU, as well the results of identification of bacterial species isolated from urine culture and the Antimicrobial Susceptibility Testing (AST). Results: From 35 study participants, 34.3% had a presumptive diagnosis of ASB and 65.7% had a diagnosis of symptomatic UTI. The predominant bacteria isolated were Escherichia coli (n=11) and Staphylococcus saprophyticus (n=2). The AST revealed a low rate of resistance to antimicrobials used for the treatment of UTI. The antimicrobial agents most prescribed was cephalexin. Further, 13 pregnant women presented comorbidities. Also, 20% presented premature delivery and 11,4% babies presented neonatal diseases. Conclusion: In this study, it was possible to know which bacterial species are commonly isolated from pregnant women urine cultures and evaluate the isolates susceptibility profile, as well as analyze the common antimicrobial therapy prescribed to these women.